ANALISIS PENGARUH STRES KERJA DAN KOMPENSASI TERHADAP KINERJA KARYAWAN Studi Pada Hotel Berbintang di Kawasan Lovina, Kabupaten Buleleng - Ketut Sudarsana (Institut Pariwisata dan Bisnis Internasional, 2016)
The purpose of this study was to determine and analyze the effect of work stress and compensation upon employee’s peformance on hotel employees in Lovina, Buleleng. This type of research was descriptive quantitative, including reviewing the effect of work stress (X1) and compensation (X2) on the dependent variable which was the performance of employees, and also analyze the effects of job stress and compensation altogether on employee performance. The research instrument used was questionnaire, and the populations in this study were 100 employees at the five-star hotel in Lovina, Buleleng.From the results of the T test and F can be seen that the stress of work and compensation partially affected employee performance in which: 1) Work stress gave negative and significant effect on employee performance; 2) Compensation gave significant positive effect on employee performance; and 3) Stress and compensation work altogether gave no significant effect on employee performance.